The art of objects : the birth of Italian industrial culture, 1878-1928. - Cottini, Luca (Toronto Italian studies., 2018)
"Presenting a cultural history of early Italian industrialism, The Art of Objects is a cutting-edge investigation of Italy's industrial culture at the turn of the 20th century, set against the political, social, and intellectual background of post-unification Italy. By adopting the unusual perspective of several objects of mass consumption, from watches, photographs, and gramophones, to toys, and furniture items, author Luca Cottini examines the transformation of these objects as they enter the market from commercial items into aesthetic and philosophical icons. By focusing on the objects' unique position at the intersection of production and consumption, art and entrepreneurship, The Art of Objects offers a more comprehensive account of the age between the Risorgimento and Fascism, encompassing the masses and the intellectual elite, technology and society, industry and the humanistic tradition. The observation of the slow formation of new languages, forms, practices, and experiences around these objects also provides an early documentation of the creative laboratory of Italy's industrial culture. Through close examination of the cultural significance of these objects as they appear in contemporary art and literature, the book ultimately investigates Italy's critical reception of industrialism, the nation's so-called "imperfect" modernization, and its ongoing quest for an original way to modernity."--